Risk factors for type 2 diabetes mellitus in Chinese rheumatoid arthritis patients from 2018 to 2022: a real-world, single-center, retrospective study - Pei, Ruomeng; Wang, Jia; He, Peifeng; Yu, Qi; Zhang, Shengxiao; Shi, Gaoxiang; Liu, Geliang; Li, Xiaofeng (Frontiers in Immunology, 2024)
In patients with rheumatoid arthritis (RA), the increased risk of concomitant type 2 diabetes mellitus (T2D) is an important contributor to increased mortality and decreased quality of life; however, the mechanisms and pathogenetic factors remain unknown. In this study, we aimed to assess the risk factors for T2D in patients with RA. We recruited 206 healthy controls and 488 patients with RA, 160 of whom had comorbid T2D. General clinical information, disease characteristics, and circulating lymphocyte levels detected using modified flow cytometry were collected from all participants. Logistic regression models adjusted for confounders were fitted to estimate the risk factors of T2D in patients with RA. The incidence of RA in patients with T2D was 15.6%. Patients with RA and T2D had a longer disease duration, higher BMI, and a higher incidence of hypertension and a family history of diabetes than those with RA but no T2D. The absolute numbers of T helper 2 cell (Th2) and Regulatory T cells (Treg) decreased in patients with RA and T2D, which led to an increase in the ratios of Th1/Th2 and Th17/Treg cells. Multivariate logistic regression analysis showed that a family history of diabetes, a higher incidence of hypertension, higher neutrophil-lymphocyte ratio (NLR) levels, lower platelet-lymphocyte ratio (PLR) levels, and fewer circulating Th2 and Treg cells were associated with an increased risk of T2D in patients with RA. The levels of peripheral lymphocytes, especially Th2 and Treg cells, are closely related to the occurrence of T2D in patients with RA; however, the influence of body mass index (BMI), family history of diabetes, and systemic inflammation should not be ignored.